Leadership, Crisis Management, and Business Continuity - Alblooshi, Moosa Ahmed Jafar Almandoos; Mohamed, Ahmad Martadha; Yusr, Maha Mohammed (South Asian Journal of Social Sciences and Humanities, 2023)
The objective of the current research was to identify the mediating role of crisis management  between leadership and business continuity. Crisis management has always been considered as a  responsibility of the leaders of the organizations. Moreover, leaders have to show their true  leadership skills during the time of crisis in order to keep things going. For meeting the  objectives of the study, the data has been collected from 384 employees working at public sector  organizations of UAE. The data has been collected by applying survey techniques and self administered questionnaires were distributed using simple random sampling. The findings from  structural equation modelling revealed that leadership has a significant direct impact over  business continuity as well as crisis management. this shows that leaders that are efficient in  leadership holds the capability to manage the crisis. Moreover, the mediating role of crisis  management between leadership and business continuity is also significant.
Keywords: leadership; business continuity; crisis management sustainability